Developing Web-Based Teaching Material Supplements To Improve Higher Order Thinking Skills (HOTs) In Mathematics Courses - Suparman Suparman Suparman; Sri Kadarwati; Eko Andy Purnomo (Program Studi Pendidikan Sejarah - Universitas Samudra, 2020)
The aim of Mathematics learning is providing the students to have logical, analytical, systematic, critical, and creative thinking skills, as well as ability to cooperate. One of the main capabilities of the student is the Higher Order Thinking Skills (HOTS). Based on the preliminary observation on students of PGSD UT Pokjar Kaliwungu 2018.1, there were still many students who had low HOTS, especially in mathematics course. This condition is proven from how the students solve the problems for a high level and unsual of difficulty exercises on mathematics courses which was very low. One of the efforts to increase HOTS capability is by using appropriate teaching materials supplements. The media learning is known to increase effectiveness, activity and improving the learning outcomes. Web Media is one of the learning media developed in mathematics learning. All in all, this study will develop a web-based learning ingredient supplement. The purpose of this study is to produce a valid teaching ingredient supplement that can enhance the student's HOTS ability. Besides, this research used a method of developing a device development with the theory of Thiagarajan, Semmel and Semmel known as 4-D models which consisted of four stages: define, design, develop, and disseminate. The method of collecting data applied the distribution of polls, observation in class and the legibility test followed by interviews. Based on the stage of teaching materials supplements obtained 1). The phase of the teaching ingredient supplement has been adapted to the students od Universitas Terbuka characteristics, mathematics and learning objectives, 2). On-hold design of the teaching materials supplement has been designed based on the results of definition Phase 3). Development results obtained a). The value of experts and practitioners of 3.94 with valid criteria, B). The results of small legibility tests resulted in a 3.82 assessment with categories usable with fewer revisions, c). A large legibility test results in the value of 4.12 with the category can be used without revision. Based on the results above it can be concluded that the teaching materials supplement is valid and can be implemented in the trial class.